The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1996
DOI: 10.1083/jcb.132.6.1037
|View full text |Cite
|
Sign up to set email alerts
|

Na+/H+ exchange activity during phagocytosis in human neutrophils: role of Fcgamma receptors and tyrosine kinases.

Abstract: Abstract. In neutrophils, binding and phagocytosis facilitate subsequent intracellular killing of microorganisms. Activity of Na+/H ÷ exchangers (NHEs) participates in these events, especially in regulation of intracellular pH (pHi) by compensating for the H ÷ load generated by the respiratory burst. Despite the importance of these functions, comparatively little is known regarding the nature and regulation of NHE(s) in neutrophils. The purpose of this study was to identify which NHE(s) are expressed in neutro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
52
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 82 publications
3
52
0
Order By: Relevance
“…In cells exhibiting recovery, the nadir occurred after 3.4 Ϯ 2.0 min (SD, n ϭ 58). The large decrease in pH i in phagocytosing neutrophils was unexpected and greatly exceeds reported responses (1,(3)(4)(5)7). This apparent discrepancy is likely attributable mainly to the smearing of time courses of individual cells by averaging, inclusion of nonresponding cells, and use of soluble stimuli in previous studies.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…In cells exhibiting recovery, the nadir occurred after 3.4 Ϯ 2.0 min (SD, n ϭ 58). The large decrease in pH i in phagocytosing neutrophils was unexpected and greatly exceeds reported responses (1,(3)(4)(5)7). This apparent discrepancy is likely attributable mainly to the smearing of time courses of individual cells by averaging, inclusion of nonresponding cells, and use of soluble stimuli in previous studies.…”
Section: Resultsmentioning
confidence: 62%
“…For 3 decades, pH i during the respiratory burst has been characterized as a small (0.05-0.1 unit) transient drop in pH i that is followed by larger (0.16-0.60 unit) prolonged alkalinization caused by Na ϩ /H ϩ antiport activity, whether the stimulus is fMLF (fMetLeuPhe, a chemotactic peptide), PMA (a PKC-activating phorbol ester), phospholipase C, or OPZ (opsonized zymosan) (1)(2)(3)(4)(5)(6)(7). In most studies, soluble stimuli were applied to populations of neutrophils.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Those similarities provide evidence to suggest that ERK may be a direct proximal component of an NHE regulatory pathway [5,6]. There is a growing awareness that tyrosine phosphorylation cycles are critical in regulating NHE activities in a number of cell types [6][7][8][9][10], as has also been shown for ERK [11]. Other studies have demonstrated that NHE and ERK activities are modulated by overlapping upstream enzymes, including phosphoinositide 3h-kinase (PI-3K), phospholipase Cγ, and PKC [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Other mechanisms responsible for pH i regulation in resting and activated eosinophils have not been investigated in detail, but it is likely that they share some similarity with neutrophils (Coakley et al, 2002;DeCoursey and Cherny, 1994;Demaurex et al, 1996;Fukushima et al, 1996;Grinstein et al, 1986;Grinstein et al, 1991). Early investigations of pH i regulation in neutrophils during the oxidative burst revealed that Na + -H + exchange (NHE-1) activity as well as the activation of proton channels was essential to prevent intracellular acidification (Coakley et al, 2002;DeCoursey and Cherny, 1994;Demaurex et al, 1996;Fukushima et al, 1996).…”
Section: Introductionmentioning
confidence: 99%